Hazard assessment and formation mechanism of debris flow outbursts in a small watershed of the Linxia Basin - Yang, Weimin; Wan, Feipeng; Ma, Siqi; Qu, Jingkai; Zhang, Chunshan; Tang, Haibing (Frontiers in Earth Science, 2023)
The Linxia Basin is located in the transition zone between the Qinghai–Tibet Plateau and the Loess Plateau in China. Collapse–landslide–debris flow geological disasters are particularly prevalent in this region. Taking a debris flow that occurred in Zhangjiayuan gully, Dongxiang County, as an example, the characteristics and formation mechanism were studied through field investigation and remote sensing interpretation methods. The hazard zoning and influence range of the debris flow were analysed under different precipitation conditions using numerical simulations. The results show that the debris flow in Zhangjiayuan gully experienced medium-to small-scale, rapid and catastrophic viscous mud flows, with activity frequencies ranging from medium to low. Because large numbers of landslides, collapses and overland flows developed on the gully bank slope, material sources for debris flows were abundant but were supplied intermittently. Induced by heavy rainfall, the landslides on the bank slipped into the gully, and then the landslide mass blocked the channel and formed a weir dam. As water converged in the gully, the dam body softened to mud, seepage deformation occurred, and the dam then burst to form a debris flow. This disaster mode represents a kind of rainfall-type landslide–blockage–debris flow disaster chain. Under varying conditions in which heavy rainfall occurs once every 10 years or once every 50 years, debris flows may break out in Zhangjiayuan gully, and the Zheda highway and the associated tunnels located below the gully are in medium–high debris flow danger zones. When a debris flow rushes out of the gully mouth and cannot be discharged in time, it accumulates and buries the highway and tunnels. Therefore, attention should be given to preventing such small-scale sudden debris flow disasters and strengthening the early warning capacity of debris flow prevention to ensure the safe operation of highway.